(untitled) (Tempo e Argumento, 2025)
Based on the connections between history and psychoanalysis in the work of historian Beatriz Nascimento (1942-1995) and psychoanalyst Neusa Santos Souza (1948-2008), this article asks how these articulations offered theoretical and methodological contributions to reflect on the layers of complexity that permeate black subjectivities in the context of racism. To this end, the article is guided by two analytical axes: the first focuses on the historical conditions of the 1970s and 1980s that favored the connections between history and psychoanalysis in the writings of Beatriz Nascimento, as well as the publication of the book Becoming Black, by psychoanalyst Neusa Santos Souza; the second puts the production of these intellectuals into dialogue, in order to make visible the potential that their reflections offer for the construction of historical narratives. Namely, because they make visible the connections between power relations and latent or explicit affective circuits that permeate the reproduction of racism.